The Influence of the Discovery Learning Model on Enhancing Motivation and Learning Outcomes in Natural and Social Sciences (IPAS) Among Students - Ria Hopipah; Hendra Sofyan; Eddy Haryanto (Postgraduate, University of Mataram, 2025)
This research was motivated by the lack of learning motivation and low student achievement in the subject of Natural and Social Sciences (IPAS). The proposed solution to this issue is the use of the Discovery Learning model. This study aims to improve motivation and learning outcomes in IPAS through the application of the Discovery Learning model among fourth-grade students at SD Negeri 82/VI Rantau Limau Kapas. This research is a Classroom Action Research (CAR) study that employs both qualitative and quantitative methods. The study was conducted in two cycles. Data collection methods included documentation, learning outcomes, and observation. The instruments used in this study were observation records, learning outcome assessments, and documentation. The results indicate an improvement in learning outcomes by 9.79% based on the pretest and posttest in cycle I and an 11.79% increase in cycle II. Additionally, student motivation in learning IPAS reached 70% in cycle I and increased to 77% in cycle II, demonstrating that the Discovery Learning model is suitable for the subjects in this study. Based on these findings, it can be concluded that the application of Discovery Learning improves both learning outcomes and student motivation in fourth-grade students at SD Negeri 82/VI Rantau Limau Kapas.